Experimental evaluation of visual flicker caused by ceiling fans. (September 2020) - Kent, Michael G.; Cheung, Toby; Li, Jiayu; Schiavon, Stefano
Abstract: Significant energy savings can be achieved by promoting elevated air speed using ceiling fans by increasing the cooling set-point temperature of an air-conditioning system. However, fan blades that obstruct the light from an artificial ceiling fixture from the relative viewing position of a building occupant could causes problems of visual flicker. We performed experiment to identify the effects of visual flicker caused by ceiling fans. Two different designs were used that had either opaque or transparent blades, which created different levels of visual flicker. These were installed in two test-rooms with similar environmental conditions. Forty-six participants took part in the study under a crossover design. Participants completed three cognitive visual tasks in both conditions: Stroop-test, switcher and digit-span tasks, respectively. Before and after completing the tasks, subjective evaluations were also given to several variables. Comparisons across the two ceiling fans showed the following results: a small and just significant reduction of performance in the digit-span task but not for the Stroop-test and switcher-task; some adverse symptoms related to visual flicker, which were not found when directly comparing the two ceiling fans against each other; and a higher reported frequency of discomfort caused by visual flicker. While the effect we uncovered in our study was small and did not influence all parameters, the exposure to visual flicker was relative short and we do not yet know how building occupants may react across a longer period. If issues of visual flicker are not addressed, it may have adverse consequences on building occupants. Graphical abstract: Image 1 Highlights: Discomfort due to visual flicker was reported more often from an opaque ceiling fan. Higher visual flicker did not affect Stroop-test and switcher-task. It produced a small and just significant reduction in the digit-span task. Visual flicker only influenced some of the variables reported by participants.